A blending rule for octane numbers of PRFs and TPRFs with ethanol. (15th September 2016) - AlRamadan, Abdullah S.; Sarathy, S. Mani; Khurshid, Muneeb; Badra, Jihad
Highlights: New experimental data for PRF and TPRF with ethanol addition are collected. A new blending rule for PRF and TPRF + ethanol octane numbers is proposed. This new blending rule consists of a linear and no-linear by mole regions. The new blending rule is more accurate and can be applied for a wide range of ON. Abstract: Ethanol is widely used as an octane booster in commercial gasoline fuels. Its oxygenated nature aids in reducing harmful emissions such as nitric oxides (NOx), soot and unburned hydrocarbons (HC). However, the non-linear octane response of ethanol blending with gasoline fuels is not completely understood because of the unknown intermolecular interactions in such blends. In general, when ethanol is blended with gasoline, the Research Octane Number (RON) and the Motor Octane Number (MON) non-linearly increase (synergistic) or decrease (antagonistic), and the non-linearity depends on the composition of the base gasoline. The complexity of commercial gasoline, comprising of hundreds of different components, makes it challenging to understand ethanol–gasoline synergistic/antagonistic blending effects. Understanding ethanol blending effects with simpler gasoline surrogates blends may enable a better understanding of ethanol blending with complex multi-component gasoline fuels. This study presents a blending rule to predict the octane numbers (ON) of ethanol/primary reference fuel (PRF; mixtures of iso-octane and n-heptane) and ethanol/toluene primary reference fuel (TPRF; mixtures of toluene, iso-octane and n-heptane) mixtures using the data available in literature and new data. The ON of ethanol blends with PRF-40, -50, and -60 were measured and compared with those from literature. Additional experimental data were collected to validate the developed model for ethanol blends of three different TPRFs having the same RON but different MON (i.e., different toluene contents). The three tested TPRF mixtures have octane ratings of RON 60.0/MON 58.0 (toluene 10.2 vol%), RON 60.0/MON 56.3 (toluene 19.8 vol%), and RON 60.0/MON 53.2 (toluene 40.2 vol%). The octane prediction model consists of linear and non-linear by mole regions. The transition point between the linear and non-linear regions is a function of the RON and MON of the base PRF and TPRF mixture. The non-linear by mole region is defined as a second-order polynomial and the combined model successfully predicts the octane number (ON) of the various ethanol/PRF and ethanol/TPRF blends with a maximum ON error of 2.7, with the majority of predictions being within the reproducibility limits. Finally, the model presented here is shown to be an improvement over that existing already in the literature.